Detection of PIK3CA E545A mutation in circulating tumor DNA of a patient affected by uterine carcinosarcoma. Issue 8 (September 2020) - Fantappiè, Giulia; Malentacchi, Francesca; Turrini, Irene; Sorbi, Flavia; Castiglione, Francesca; Vergoni, Federica; Ammatuna, Carlo; Antonuzzo, Lorenzo; Fambrini, Massimiliano; Noci, Ivo; Pillozzi, Serena
Abstract : Uterine carcinosarcomas are biphasic neoplasms consisting of mixed epithelial and mesenchymal elements, representing less than 5% of all uterine malignancies. Carcinosarcomas are rare, although the most common cause of uterine cancer-specific death. Few information is available on the pathogenesis, and molecular characterization is poorly investigated. Consequently, the treatment has not changed over the last years and is far too being tailored, consisting of surgery and traditional chemotherapy and radiotherapy. Molecular characterization of liquid biopsy by circulating tumor DNA (ctDNA)/circulating cell-free DNA (ccfDNA) evaluation in a patient with uterine carcinosarcoma. Here, we describe a case report of an 83-year-old woman with carcinosarcomas, stage T3aN0M0. Cancer cells did not express estrogen nor progesterone receptors, while p53 and p16 were positive. Molecular characterization of ccfDNA and of ctDNA was performed by quantitative PCR, amplification-refractory mutation system technology. The presence of phosphatidylInositol-4, 5-bisphosphate 3-Kinase catalytic subunit alpha p.E545A mutation was detected in plasma. This approach may suggest the use of liquid biopsy and the development of specific targeted therapy for precision personalized medicine even in rare carcinosarcomas.